Shock-induced large-depth gradient microstructure in commercial pure titanium subjected to explosive hardening. (January 2022) - Guo, Yansong; Zhou, Qiang; Ran, Chun; Liu, Rui; Arab, Ali; Ren, Yeping; Chen, Pengwan
Graphical abstract: Highlights: Large-depth gradient hardness distribution with depth of 2.5 mm was produced in commercially pure titanium by explosive hardening. Gradient α-ω phase transition, gradient grain size, gradient twining and gradient dislocation was occurred in commercially pure titanium by explosive hardening. Two types of grain refinement modes, multi-directional twinning-twinning interaction and twinning-dislocation wall interaction, were revealed. Abstract: Explosive hardening of commercial pure titanium plate was conducted by a thin-layer high-detonation-velocity explosive. The nanoindentation and Vickers hardness tests of the treated titanium plates along the depth of shock loading were performed. The microstructures along the depth were characterized by using different methods, including X-Ray Diffraction, Optical Microscopy, Electron Back-Scattered Diffraction and Transmission Electron Microscopy. Experimental results showed that large-depth gradient hardness distribution with depth of 2.5 mm was produced in CP titanium by explosive hardening. There are two gradient hardened layers, ultra-hardened layer with a depth of 0–40 μm and a hardness increase of ∼400%, sub-hardened layer with a depth of 40 μm-2500 μm and a hardness increase of 54.3%. Gradient microstructures with different characteristics were observed, including gradient α-ω phase transition, gradient grain size, gradient twining and gradient dislocation. The area of gradient microstructure is consistence with that of gradient hardness distribution. Grain refinement/α-ω phase transition mainly contributed to hardness sharply increasing in ultra-hardened layer. High-density dislocation/twining mainly contributed to hardness increasing in the sub-hardened layer. Finally, the formation mechanism of gradient microstructures and grain refinement mechanism was detailly discussed.